Odpowiedzi

Najlepsza Odpowiedź!
2009-12-13T14:16:07+01:00
3(2x+6)-1=5(x-4)+9
6x +18 -1 = 5x -20 +9
6x + 17 = 5x -11
6x -5x = -11 -17
x = -28

(x+1)²=(x-2)²
x² +2x +1 = x² - 4x +4
x² +2x -x² +4x = 4 -1
6x = 3
x = 3/6
x = ½

3-(x-2)=x²-(x+1)²
3 - x +2 = x² -( x² +2x +1)
-x +5 = x² - x² -2x -1
-x +5 = -2x -1
-x +2x = -1 -5
x = -6

(2x-3)²-(2+2x)²=0
4x² -12x +9 -( 4 +8x +4x²)= 0
4x² -12x +9 - 4 -8x - 4x² = 0
-20x + 5 = 0
-20x = -5
x = (-5) : (-20)
x = 5/20
x = ¼
2009-12-13T14:19:46+01:00
3(2x+6)-1=5(x-4)+9
6x+18-1=5x-20+9
6x-5x=-20+9+1-18
x=-28

(x+1)²=(x-2)²
x²+2x+1=x²-4x+4
x²-x²+2x+4x=4-1
6x=3/:6
x=0,5

3-(x-2)=x²-(x+1)²
3-x+2=x²-(x²+2x+1)
5-x=x²-x²-2x-1
-x+2x=-1-5
x=-6

(2x-3)²-(2+2x)²=0
4x²-12x+9-(4+8x+4x²)=0
4x²-12x+9-4-8x-4x²=0
-20x=-5/:(-20)
x=¼
2009-12-13T14:24:03+01:00
3(2x+6)-1=5(x-4)+9
6x+18-1=5x-20+9
6x-5x=-11-17
x=-28


(x+1)²=(x-2)²
x²+2x+1=x²-4x+4
2x+1=-4x+4
6x=3
x=0,5


3-(x-2)=x²-(x+1)²
3-x+2=x²-x²-2x-1
5-x=-2x-1
-x+2x=-1-5
x=-6


(2x-3)²-(2+2x)²=0
4x²-12x+9-4-8x-4x²=0
-20x=-5
x=1/4